Analisis Determinan Faktor Cash Holding pada Subsektor Property and Real Estate yang Terdaftar di Bursa Efek Indonesia - Suryani, Jely; Jonathan, LCA Robin; Irwan, Sayid (LPPM University 17 Agustus 1945 Samarinda, 2024)
This study aims to determine and analyze the effect of Growth Opportunity, Leverage (DAR), Net Working Capital, Operating Cash Flow on Cash Holding in the Property and Real Estate Subsector listed on the Indonesia Stock Exchange in 2021.The sampling in this study used purposive sampling techniques, with the final sample obtained was 50 companies. The type of data used is secondary data obtained from financial statements published through IDX. The analysis technique used is multiple linear regression analysis with the use of SPSS program version 25.The results of the analysis explain that (1) Growth opportunity has a negative insignificant effect on Cash holding (2) Leverage (DAR) has a positive insignificant effect on Cash holding (3) Net Working Capital has a positive insignificant effect on Cash holding (4) Operating cash flow has a significant positive effect on Cash holding (5) Growth opportunity, Leverage (DAR), Net Working Capital, Operating cash flow silmutant has a significant positive effect.